Georges Bataille: a experiência literária - Luis Fernando Gonçalves Balby (2020)
This thesis focuses on the literary experience of Georges Bataille and seeks to clarify the form and the contents that the writer claimed to be essential to literature and poetry. The text is an analysis guided by the tools of criticism offered by psychoanalysis and elaborated mainly from the textuality of Bataille himself, as well as through the textuality of Sade and Nietzsche, in addition to other writers with whom he established communication. The architecture of the thesis was designed to mirror the figure that illustrates the covers of the magazine Acéphale (who had Bataille as the main contributor) and also the perspective of the lacerated anthropomorphism supported by the writer. We highlight, from that figure and from that perspective, some of the signifiers that we consider the most relevant for the writing of the thesis' chapters: the big toe, the eye, the absence of the head and the cleft - signifiers analyzed not from their conformation with themselves, but taking into account, in each case, what the writer presented as being relative to the dimension of the formless. The literary experience is then written by Bataille as a dimension beyond the simple presentation and construction of meanings, that is, as a dimension that escapes the established knowledge and that is placed in a field that is not that of discourse or that of the system. The method operated by Bataille's writing is to open the signifiers just as, for him, the human body presents itself as a sign of opening and becoming. Thus, just as the human body is marked by its inscription in the dimension of not-knowing, Bataille's literary experience consists of the poetic treatment that he gives to the signifiers of that body and that his writing presents as vanishing points: as a language that transgresses the rational and the useful and that moves towards the forms of the sacred and the ecstasy.